2023
DOI: 10.4236/jbm.2023.114022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Attention and Short-Term Memory Loss by EEG Workload Estimation

Abstract: Mental workload plays a vital role in cognitive impairment. The impairment refers to a person's difficulty in remembering, receiving new information, learning new things, concentrating, or making decisions that seriously affect everyday life. In this paper, the simultaneous capacity (SIMKAP) experimentbased EEG workload analysis was presented using 45 subjects for multitasking mental workload estimation with subject wise attention loss calculation as well as short term memory loss measurement. Using an open ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(42 reference statements)
2
0
0
Order By: Relevance
“…2.6∼19.5 s for a fast reader [13], and 5.3 ∼ 30.1 s for an average reader of novels, values that are well-supported by the experiments reported in the literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
supporting
confidence: 84%
See 1 more Smart Citation
“…2.6∼19.5 s for a fast reader [13], and 5.3 ∼ 30.1 s for an average reader of novels, values that are well-supported by the experiments reported in the literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
supporting
confidence: 84%
“…We have shown that the capacity (expressed in words) required to process a sentence ranges from 8.3 to 61.2 words, values that can be converted into time by assuming a reading speed. This conversion gives the range 2.6~19.5 s for a fast reader [13], and 5.3~30.1 s for an average reader of novels, values that are well-supported by the experiments reported in the literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
supporting
confidence: 79%